The Best of Technology Writing 2006 - Brendan I. Koerner (University of Michigan Press, 2006)
The Best of Technology Writing 2006 brings together some of the most important, timely, and just plain readable writing in the fast-paced, high-stakes field of technology. The first annual collection to target this vibrant and versatile area, The Best of Technology Writing 2006 features innovative work from an unusually diverse array of writers: best-selling authors, noted academics, and indie journalists and bloggers. The culmination of an open, on-line nominating process, this collection covers topics ranging from jetpacks, to the ethics of genetically cloned pets, to the meaning of life in the information age. By turns epic and intimate, serious and playful, The Best of Technology Writing 2006 captures the vitality, importance, and complexity of technology today.